KAJIAN PELAKSANAAN UU NO 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS TERHADAP PERJANJIAN KREDIT BANK DENGAN DEBITUR PERSEROAN TERBATAS BERIKUT AKIBAT YURIDISNYA (STUDI KASUS PADA KANTOR CABANG BRI MALANG KAWI) - , Eka Ahmad Djatnika; , Sularto, S.H. C.N. M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Banking in Indonesiaâs main business nowadays is define what the Act No.10 of 1998 stated, which is collects public funds and then give it back in the form of credit or financing in order to improve the lives of many Limited Liability Companies must adapt its Articles of Association with the enactment of Act No.40 of 2007 regarding Limited Liability Company on August 16, 2007 in lieu of Act No.1 of 1995. This thesis examines the implementation of changes to Act no.40 of 2007 is related to the Credit Agreement PT Bank Rakyat Indonesia (Persero) Tbk Company Limited following the debtor due to juridical. PT Bank Rakyat Indonesia (Persero) Tbk. as a Limited Company and BRI borrowers in the form of a Limited Liability Company has adjusted its Articles of Association with the enactment of Act No. 40 of 2007 regarding Limited Liability Company. Binding of the Bank Credit Agreement and Limited Warranty for the debtor has provided adequate protection against BRI